SuperMEN1 Pituitary, Parathyroid and Pancreas - Balogh, Katalin; Patocs, Attila (Advances in Experimental Medicine and Biology, 2010)
The vast expansion in research on tumorigenesis has greatly increased our understanding of tumor development in patients with inherited endocrine tumor syndromes. This book provides an up-to-date summaryfrom clinical basics and latest follow-up guidelines to the most recent molecular findings in multiple endocrine neoplasia Type I syndrome. Articles have been assembled by acknowledged experts in their respective fields to provide current perspectives on the clinical and genetic backgroundsofthis syndrome and to review carefully the latest discoveries concerning the possible functions and interactions ofmenin, the protein encoded by the MEN1gene,including itspossible role incell cycle regulation,hematopoiesis,and bone development. The goal ofthe book is also to present the most recent findings and the broadest aspects of the role of menin in tumorigenesis of the endocrine glands involved in MEN I syndrome (pituitary, parathyroid, endocrine pancreas and adrenal). The connection between the basic experimental and clinical points of view are highlighted through a discussion on animal models, which explores the field in both an inspiring and questioning manner with a focus on areas that remain to be clarified. Our goal was to bring together clinicians and basic researchers who represent a wide range of interests in this particular field of endocrine oncology. Presentingacomprehensive and current overviewofbasic experimental and clinical findings, this book can bring us closer to understanding endocrine tumorigenesis in multiple endocrine neoplasia Type I. Katalin Balogh, MD, PhD Attita Patocs, MD, MSc, PhD v ABOUT THEEDITORS. . .